2011
DOI: 10.1007/s10578-011-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Reading Difficulties in Early Elementary School: Evidence for Unidirectional- or Bi-Directional Relations?

Abstract: The present study examined competing models of the bi-directional influences of anxiety and reading achievement. Participants were 153 ethnically-diverse children (84 male, 69 female) from general education classes evaluated in the winter and spring of their first-grade academic year. Children completed standardized measures of reading achievement involving decoding and fluency along with an anxiety rating scale. Hierarchical linear regression analyses revealed that separation anxiety symptoms were negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
88
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 52 publications
13
88
2
5
Order By: Relevance
“…The findings are similar to those of Huberty (2009) who reported that characteristics of anxiety can affect students behaviorally, cognitively, and physiologically, for example, high stakes testing can be very difficult for students with anxiety. Grills-Taquechel, Fletcher, Vaughn, & Stuebing (2012) study reported that, students who had lower reading scores at the beginning of the study tended to decrease their harm avoidance tendencies at the end of the study. A decrease in harm avoidance tendencies means the students were not as concerned with reading correctly.…”
Section: Findings On Relationship Between Level Of Anxiety and Studenmentioning
confidence: 93%
“…The findings are similar to those of Huberty (2009) who reported that characteristics of anxiety can affect students behaviorally, cognitively, and physiologically, for example, high stakes testing can be very difficult for students with anxiety. Grills-Taquechel, Fletcher, Vaughn, & Stuebing (2012) study reported that, students who had lower reading scores at the beginning of the study tended to decrease their harm avoidance tendencies at the end of the study. A decrease in harm avoidance tendencies means the students were not as concerned with reading correctly.…”
Section: Findings On Relationship Between Level Of Anxiety and Studenmentioning
confidence: 93%
“…To summarize, students with school under-achievement are more likely to show lower global self-esteem and to report increasing anxious and depressive symptomatology than typical achievers [32][33][34].…”
Section: Depression In Childrenmentioning
confidence: 98%
“…This reason for referral was indicated by parents at the time of referral. Interestingly, only 4.7 % of our sample diagnosed with GAD (as either primary or secondary) had ''anxiety'' reported as the reason for referral, although anxiety-related problems may have been reflected in broader domains such as ''academic problems'' given the linkage between anxiety and schoolrelated impairment [15][16][17][18].…”
Section: Participantsmentioning
confidence: 99%